Traumatic ruptures of the Achilles tendon - Caritat, Ricardo J. (Cirugía del Uruguay, 2020)
Session of April 21st, 1938. Work of the Traumatology Service of the Surgical Clinic of Prof. Blanco Acevedo. - Pasteur Hospital.